Large-scale geographic patterns of diversity and community structure of pelagic crustacean zooplankton in Canadian lakes - Pinel-Alloul, Bernadette; André, Adrien; Legendre, Pierre; Cardille, Jeffrey A.; Patalas, Kasimierz; Salki, Alex (Global ecology and biogeography, 2013)
Aim: We tested the energy and metabolic theories for explaining diversity patterns of crustacean Zooplankton in Canadian lakes, and evaluated the influence of regional and local environments on community structure. Location: The 1665 studied lakes are distributed across Canada in 47 ecoprovinces. Methods: Our database included the occurrence of 83 pelagic crustacean species. The regional species richness in each ecoprovince was estimated using the average local species richness per lake and the first-order jackknife diversity index. Using a principal component plot and forward selection in a multiple regression we identified the most important predictors of regional species richness estimates. We tested the predictions of the species richness-energy hypothesis using climatic variables at regional scale, and of the metabolic theory using the inverse of air temperature. To evaluate the influence of regional and local environmental drivers, we carried out a redundancy analysis between crustacean species occurrences and regional climate and lake environmental factors on a subset of 458 lakes. Results: Estimates of pelagic crustacean species richness in Canadian ecoprovinces varied from 3 to 10 species per lake (average local species richness) or 8 to 52 species per ecoprovince (Jackknife diversity index). Our study fully supports the species richness-energy hypothesis and partially the metabolic theory. Mean daily global solar radiation was the most important regional predictor, explaining 51% of the variation in the regional species richness among ecoprovinces. Together, regional climate and local lake environment accounted for 31% of the total variation in community structure. Regional-scale energy variables accounted for 24% of the total explained variation, whereas local-scale lake conditions had less influence (2%). Main conclusions: The richness-energy theory explains diversity patterns of freshwater crustacean zooplankton in Canadian ecoprovinces. Solar radiation is the best predictor explaining regional species richness in ecoprovinces and community structure of pelagic crustaceans in Canadian lakes.